FENOMENA POLITISASI MESJID TINJAUAN POLITICAL PROCESS THEORY - Ilmi, Muhammad Hafidz; Abdillah, Muhammad Torieq (UIN ANTASARI BANJARMASIN, 2023)
Abstract: One of the issues that arises ahead of the democratic festivities is the politicization of places of worship, in this case, mosques. This study aims to elaborate on how the political process theory views the phenomenon of mosque politicization. The writing is based on data published in various media, both print and electronic. This research is of a qualitative descriptive type. The results indicate that the strategies offered from the analysis using the political process theory involve the revitalization of the role and function of mosques, with optional solutions such as supporting and utilizing the government’s latest program, the Mosque as the Pioneer of Religious Moderation (MPMB), and enhancing the literacy of mosque stakeholders. The study is limited to the data used, allowing for further research with a broader data scope and more comprehensive theories. Keywords: Phenomenon; Mosque Politicization; Political Process Theory Abstrak: Salah satu persoalan yang mengemuka jelang pesta demokrasi adalah politisasi tempat ibadah, dalam hal ini mesjid. Penelitian ini bertujuan untuk menguraikan bagaimana political process theory memandang fenomena politisasi mesjid. Penulisan ini berdasarkan data yang dimuat di berbagai media, baik cetak maupun elektronik. Penelitian ini berjenis deskriptif kualitatif. Hasil penelitian menunjukkan bahwa strategi yang ditawarkan dari analisis menggunakan political process theory melibatkan revitalisasi peran dan fungsi mesjid, dengan solusi opsional seperti mendukung dan memanfaatkan program terbaru pemerintah, yaitu Masjid sebagai Pelopor Moderasi Beragama (MPMB), dan meningkatkan literasi pemangku kepentingan mesjid. Kajian hanya sebatas data yang digunakan, sehingga memungkinkan dilakukannya penelitian selanjutnya dengan cakupan data yang lebih luas dan teori yang lebih komprehensif Kata Kunci: Fenomena; Politisasi Mesjid; Political Process Theory